[Ca2+]i oscillations in ASM: Relationship with persistent airflow obstruction in asthma. Issue 5 (22nd May 2014) - Sweeney, David; Hollins, Fay; Gomez, Edith; Saunders, Ruth; Challiss, R.A. John; Brightling, Christopher E.
<x xml:space="preserve">Abstract</x> The cause of airway smooth muscle (ASM) hypercontractility in asthma is not fully understood. The relationship of spontaneous intracellular calcium oscillation frequency in ASM to asthma severity was investigated. Oscillations were increased in subjects with impaired lung function abolished by extracellular calcium removal, attenuated by caffeine and unaffected by verapamil or nitrendipine. Whether modulation of increased spontaneous intracellular calcium oscillations in ASM from patients with impaired lung function represents a therapeutic target warrants further investigation.